Research of humanization transformations of the higher education system of Ukraine at the end of the 20th - early 21st centuries (1985-2012) - Yevsovych, Roman (Journal of Education, Health and Sport, 2021)
The article analyzes the theoretical and practical foundations of humanization and humanization of domestic higher education in the late twentieth - early twenty-first century. Based on a comprehensive historical and pedagogical analysis, the research identifies and characterizes the essence of humanization transformations of higher education in Ukraine. The research hypothesis is based on the thesis that special value-oriented pedagogical conditions in the process of professional training are a prerequisite for the acquisition of values and sense experience of future specialists in foreign philology, which creates important prerequisites for the formation of axiological competencies. The proposed study is aimed at determining the level of formation of values and sense experience among future specialists in foreign philology at the initial and final stages of the experiment. The paper analyzes the key concepts, the essence of humanization and humanitarianization and its established features. The main periods are singled out: the first (1985-1990) - directive humanization and humanitarianization of higher education in Ukraine; the second (1990-1995) - humanization and humanitarianization in the process of higher education reform; the third (1995-2004) - normative-legal institutionalization of the process of humanization and humanitarianization of higher education; fourth (2005-2012) - international integration of higher education in Ukraine in the process of humanization and humanitarianization with their inherent trends. The article has comprehensively researched tendencies, ways, innovative technologies of humanization and humanitarianization of higher education of Ukraine, the possibilities of the improvement taking into account the European educational standards, accumulated positive experience, national traditions and modern tendencies in the organization of higher education in the conditions of Ukraine’s integration into the European educational space. The course of scientific research has proved that the axiological approach to humanization and humanitarianization of the process of training future specialists in higher education is to focus the learning process on personal growth of the student, ensuring his/her comprehensive, cultural, socio-moral and professional development. The teaching of professional and methodological disciplines does not act as a transfer of information, but as activation and stimulation of the process of independent search for one’s own value position in relation to the world, formation of worldview, development of youth perception, ensuring students’ understanding of human values and harmony of human relations. The results of the study have confirmed the effectiveness of the author’s approach to the formation of the humanistic orientation of future professionals in the higher education system of Ukraine during the study period. The research on the humanization and humanitarianization of higher education in Ukraine in the late twentieth - early twenty-first centuries made it possible to involve in scientific circulation a wide range of materials that are representative in nature and reproduce certain aspects of the studied problem, and therefore need to be generalized. Various principles, methods and techniques of modern methodology used in the process of the research have allowed avoiding subjective and biased assessments, ensuring the scientific validity of the results obtained during the research, confirming a sufficiently representative character of the identified sources.